Burden of proof: a historical and theoretical analysis of some aspects of the following concepts in relation to the interpretation of Section 82 of Act 58 of 1962: income, assessment, objection and appeal - Rubinsztein, Aron Natan (Centre for Law and Society, 2026)
Even though Act 58 of 1962 is the culmination of a slow and complex evolution, some of the sections of the Act are virtually identical to sections of the New South Wales Act 1895 (59 Victoria 15). It is unfortunate indeed that the framework of the Act, for the purpose of the statutory formula, is considerably inferior to the framework of Act 41 of 1917, Act 40 of 1925 and Act 31 of 1941. The Act itself has negligible impact for the understanding and interpretation of the burden of proof in its context. The golden age of "burden of proof" is Act 31 of 1941. Some of the erroneous conceptions concerning "burden of proof" have become so fossilized, that the interpretation of the burden of proof provisions of the Act, in terms of the language used by the Act, becomes daring and controversial.